The use of BPMN to characterize processes Importance of Business Process Modeling in the health area - Luciano, Bruna dos Santos (2022)
Currently, a healthcare institution, of whatever type, needs a detailed management of all the processes involved, so that these organizations and their professionals can provide their services more efficiently, and archive the goals of the institution. In health institutions, the processes aren’t identified, procedure’s manuals are difficult to interpret and often, the professionals don’t have time to consult them. Business Process Management can be a possible solution, used for managing the processes in this type of institution, decreasing human and technical errors. This thesis aims to study the importance and the need to implement the Business Process Modelling and Notation (BPMN) in healthcare institutions, through the analysis of interviews to different professionals who work with this notation in different areas, and compare these results, with previous studies also in the healthcare area. We conclude that the implementation of BPMN can indeed be used in the healthcare institutions, and with the necessary training and engagement from all the professionals, can be a benefit, in order to improve the institutions services.